Effects of an ethinyl estradiol/gestodene transdermal contraceptive patch on the endometrium: a single-center, uncontrolled study. (January 2014) - Merz, Martin; Grunert, Julia
Aim: This study aims to investigate the effect of a transdermal contraceptive patch containing ethinyl estradiol and gestodene on endometrial proliferation over 1 year.Materials & methods: In this open-label, uncontrolled, Phase IIb study, women (aged 18–35 years) used the patch for 13 cycles of 28 days. The primary variable was histologic endometrial effects at cycle 13. Secondary objectives included contraceptive efficacy and safety.Results: Overall, 89 women were treated. At all visits, endometrial biopsies were devoid of any abnormalities. One woman became pregnant. The patch was well tolerated, with no safety concerns.Conclusion: The ethinyl estradiol and gestodene patch had an endometrial effect consistent with suppression of endometrial proliferation in most patients. No endometrial abnormalities or other concerns were reported; compliance was good.